Radiographic Assessment of Anatomic Risk Factors Associated with Acute, Lateral Patellar Dislocation in the Immature Knee - Thai Trinh; Andrew Mundy; Matthew Beran; Kevin Klingele (MDPI AG, 2016)
Acute patellar dislocation remains a common injury in both adult and pediatric patients. Non-operative management has been advocated for patients without a history of recurrent instability. Although pathologic thresholds for consideration of operative management have previously been reported in adults, it is largely unknown in children. A retrospective review of all skeletally immature patients diagnosed with acute lateral patellar dislocation who had MRI imaging were included for analysis. An age-based control group was also identified. Six radiographic measurements were compared: lateral trochlear inclination (LTI), trochlear facet asymmetry (TFA), trochlear depth (TD), tibial tuberosity-trochlear groove (TT-TG), sulcus angle (SA) and patellar height ratio. A total of 178 patients were included for analysis (study: n = 108, control: n = 70). The mean age of patients in the study and control groups was 13.7 and 12.1 years respectively (p ≤ 0.001). Study group patients had significant differences in all radiographic measurements including a decreased LTI (p < 0.001), increased TFA (p < 0.001) and SA (p < 0.001). The mean trochlear depth was 3.4 mm and 5.6 mm for patients in the study and control groups respectively (p < 0.001). Study group patients had an increased patellar height ratio (p < 0.001) and TT-TG distance (p < 0.001). Morphologic abnormalities may predispose skeletally immature patients to an increased risk of acute lateral patellar instability.